STRATEGI PUBLIC RELATIONS PT. ALAM SUTERA REALTY TBK. DALAM MEMBENTUK CITRA GARUDA WISNU KENCANA CULTURAL PARK SEBAGAI LANDMARK PARIWISATA BALI TAHUN 2018 - Arini Dewi, Ida Ayu Putu; Pascarani, Ni Nyoman Dewi; Pradipta, Ade Devia (E-Jurnal Medium, 2019)
ABSTRACT This study is a descriptive qualitative study by collecting the data from the interview, observation and documentation to get detailed description about the role and public relation strategy of PT. Alam Sutera Realty Tbk. in forming the image of Garuda Wisnu Kencana Cultural Park as the Bali tourism landmark 2018. The result of this research showed public relation strategy of PT. Alam Sutera Realty Tbk has not maximally implementing the seven strategies which are in accordance to the concept used in this study in forming the image of Garuda Wisnu Kencana Cultural Park as the Bali tourism landmark 2018. The lack of practitioner in public relations is also one of the important factor in the successful of forming the image of Garuda Wisnu Kencana Cultural Park as the Bali tourism landmark 2018.   Keywords : Image, Garuda Wisnu Kencana Cultural Park, Landmark, Public Relations, Strategy